Media and Digital Marketing: Bibliomatrix Analysis using R (Future Research Directions) - Minawati Wening; Tinik Sugiati; Erick Karunia; Shalahuddin Shalahuddin (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study aims to analyze the development of research trends on social media and digital marketing in scientific articles indexed in the Scopus database during 2020–2025. The research uses a descriptive quantitative approach with bibliometric methods to map patterns of scientific publications, researcher collaboration, and the development of research topics in the field. Research data were obtained from the Scopus database using the PRISMA approach, yielding 544 articles that met the inclusion criteria. Data analysis was carried out in RStudio using the Bibliometrix package and the BiblioShiny interface to identify annual publication trends, author productivity, country contributions, citation analysis, and research topic mapping. The results showed that publications on social media marketing increased significantly each year during the study period. In addition, it was found that several countries make a dominant contribution to publications, and that there has been an increase in international collaboration in digital marketing research. Thematic analysis also shows that topics such as social media marketing, consumer engagement, and digital strategy are the main focus in the scientific literature. This research contributes to understanding the direction of development in social media-based digital marketing research. It provides a reference for academics, practitioners, and policymakers to develop more effective digital marketing strategies in the era of digital transformation.